2008
DOI: 10.1044/1092-4388(2008/07-0259)
|View full text |Cite
|
Sign up to set email alerts
|

Reading Achievement Growth in Children With Language Impairments

Abstract: Purpose This study examined the reading achievement growth of children with language impairments (LI) across the school grades. The authors sought to determine whether children with LI demonstrate a delayed, deficit, or cumulative pattern of reading achievement growth when compared with children with typical language (TL). Method A group of 225 children with LI and a group of 379 children with TL were identified in kindergarten and were administered multiple measures of word recognition and reading comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
124
3
12

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(147 citation statements)
references
References 41 publications
8
124
3
12
Order By: Relevance
“…There is a large body of work showing that speech impairments are associated with sharply lower scores on tests of reading and math (Catts 1993;Walker et al 1994;Stothard et al 1998;Catts et al 2002;Knox 2002;Nathan et al 2004;Catts et al 2008;Harrison et al 2009;Eide and Showalter 2010;Law et al 2010). There is also evidence, albeit weaker, that children with speech impairments go on to receive fewer years of education than their counterparts without speech impairments (Snowling et al 2001;Johnson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…There is a large body of work showing that speech impairments are associated with sharply lower scores on tests of reading and math (Catts 1993;Walker et al 1994;Stothard et al 1998;Catts et al 2002;Knox 2002;Nathan et al 2004;Catts et al 2008;Harrison et al 2009;Eide and Showalter 2010;Law et al 2010). There is also evidence, albeit weaker, that children with speech impairments go on to receive fewer years of education than their counterparts without speech impairments (Snowling et al 2001;Johnson et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Speech production difficulties, experienced by many children with DS (Cleland, Wood, Hardcastle, Wishart, & Timmins, 2010) and some children with SLI (Shriberg, Tomblin, & McSweeney, 1999) may also limit responses. Semantic priming experiments (e.g., Nation & Snowling, 1999) offer alternative, implicit assessments of semantic association, although assessments based on printed words are inappropriate for some children with SLI or with DS with more limited reading skills (e.g., Catts, Bridges, Little, & Tomblin, 2008;Laws, 2010). Auditory lexical decision tasks can reveal the strength of semantic associations (e.g., Pizzioli & Schelstrate, 2011) but performance could be affected by hearing loss, which is common in DS (Davies, 1996), or by severely limited memory spans that, in some individuals with DS, do not extend to two items (e.g., Laws & Gunn, 2004).…”
Section: Vocabulary and Semantic Knowledge In Sli And Down Syndromementioning
confidence: 99%
“…These include literacy (Botting, Simkin & Conti-Ramsden, 2006;Catts, Fey, Tomblin & Zhang, 2002, Catts, Bridges, Little & Tomblin, 2008Stothard, Snowling, Bishop, Chipchase & Kaplan, 1998), academic attainment (Conti-Ramsden, Durkin, Simkin & Knox, 2009;Knox, 2002;Snowling et al, 2001) and social, emotional and behavioral functioning (Beitchman et al, 1996;Botting & Conti-Ramsden, 2000;Clegg et al, 2005). All the studies cited above are of clinically referred participants with a confirmed diagnosis of SLCD.…”
Section: Language and Communication Difficulties In Adolescentsmentioning
confidence: 99%